AKULTURASI BUDAYA AKULTURASI BUDAYA JAWA DAN AGAMA BUDDHA DALAM PUJA BAKTI BUDDHA JAWI WISNU: Studi Kasus Di Dusun Kutorejo Desa Kalipait Kecamatan Tegaldlimo Kabupaten Banyuwangi - Dayu Dhira Wintako Dayu; Suharno Suharno; Danang Try Purnomo (STABN Raden Wijaya Wonogiri, 2021)
Abstract The result of this research was Jawi Vishnu Buddhist in Kutorejo Hamlet first entered and developed in 1955 brought by a character named Father Resi Kusuma Dewa. Jawi Vishnu Buddhist grew rapidly throughout Kutorejo Hamlet. Jawi Wisnu Buddhist experienced a decrease in the number of followers due to the G30/SPKI incident, Jawi Vishnu Buddhists united with Buddhism until now. There was a form of acculturation of Javanese culture and Buddhism in the process of Buddhist worship of Jawi Vishnu. This form of acculturation was found in the monastery building and the clothes of the Jawi Vishnu Buddhists who still wore Javanese traditional clothes. The offerings used in the Buddhist Worship process was a set of banana that was equipped with sekar kinang and also sari or money, Javanese mantras that had been previously believed. there was an effort to maintain the Buddhist tradition of Jawi Vishnu at Vihara Jati Damaloka. It was that the elders continued to invite the younger generation to participate in the management of the monastery. In addition, the administrators of the Vihara and Buddhist Jawi elders also cooperated with the government. In this case was the Directorate General of Buddhist Guidance in the formation of the Jawi Buddhist community.